2019
DOI: 10.1111/ggi.13624
|View full text |Cite
|
Sign up to set email alerts
|

Emergency surgery and American Society of Anesthesiologists physical status score are the most influential risk factors of death in nonagenarian surgical patients

Abstract: Aim The number of nonagenarians undergoing surgery has increased considerably in recent decades as a result of population aging. Greater knowledge of the most influential factors affecting perioperative morbidity and mortality would improve the quality of care and provision of health resources for these patients. The objective of the present study was to analyze the perioperative mortality, and its most determinant factors, among nonagenarian patients who underwent a surgical procedure in the Department of Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Comorbidity measured by the Charlson Comorbidity Index in the general population has been related to anastomotic leak, postoperative complications and death in Chinese patients [24], but there are not published data focused on this topic specifically in nonagenarians. In a previously reported study [25], we found that ASA score and emergency surgery were the most significant factors for operative mortality in a general nonagenarian population, but these variables lost their predictive value for postoperative complications in this subgroup of nonagenarian patients operated on for CRC. Other authors [13] have also reported than older age, higher ASA score, anemia, and lower serum albumin increased postoperative complications.…”
Section: Discussionmentioning
confidence: 53%
“…Comorbidity measured by the Charlson Comorbidity Index in the general population has been related to anastomotic leak, postoperative complications and death in Chinese patients [24], but there are not published data focused on this topic specifically in nonagenarians. In a previously reported study [25], we found that ASA score and emergency surgery were the most significant factors for operative mortality in a general nonagenarian population, but these variables lost their predictive value for postoperative complications in this subgroup of nonagenarian patients operated on for CRC. Other authors [13] have also reported than older age, higher ASA score, anemia, and lower serum albumin increased postoperative complications.…”
Section: Discussionmentioning
confidence: 53%
“…As revealed by findings of studies in Ethiopia,26 Kenya,22 Rwanda,33 Spain40 and the USA,5 emergency surgery was found to be a significant predictor of postoperative mortality. The best explanation might be that patients with emergency surgical conditions have an advanced disease stage in which an impaired immune system leads to sepsis and increases the likelihood of death after surgery 41.…”
Section: Discussionmentioning
confidence: 92%
“…In our setting, ASA classification, emergency surgery and CHF were independent risk factors for mortality and morbidity. Several studies concluded that ASA classification provides a good indication of adverse postoperative outcomes in patients aged ≥90 years [ 2 , 13 , 14 ]. ASA III (60.4%) predominated in the present study and was similar (51.8%) to the previous study [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of people aged ≥90 around the world is estimated to be nearly fourfold by 2050 (from 21 million in 2020 to 77 million) and will increase nearly eleven-fold by 2100 [ 1 ]. Because of life extension and advances in surgical and anesthetic techniques in recent decades, the number of older patients undergoing surgery has increased, and the population of patients aged ≥90 who need surgical intervention has also increased [ 2 ].…”
Section: Introductionmentioning
confidence: 99%